A systematic review on activation of developmental genes and the developmental block in buffalo embryos - Kennady, Vijayalakshmy; Biswal, Jyotsnarani; Rahman, Habibar (2020)
Providing desired in-vitro conditions for maturation of oocytes, fertilisation and embryo development are necessary to achieve greater success rate in in-vitro embryo production. However maintenance of these systems are more complicated and challenging than the standard in-vitro culture, this is mainly because of the difference in the environments where the gametes and embryos have to pass through during their in vivo development. With the improvement in various culture medium and culture conditions, the developmental rate of in vitro culture embryos are found to be high, but in majority of the cases zygotes stop their development within certain cell cycles after the initiation of cleavage. This is mainly because of the developmental block which arises mostly at the eight-cell stage and it varies with species. Developmental block is found to have a correlation with the quality of the cytoplasm in the oocyte. Oocyte is the principle source provider of all mRNAs and proteins that are required by the embryo to reach fourth or fifth cell cycle. Embryos that are failed to transcribe their own genome cannot develop further. The present review describes the developmental block, activation of the developmental genes in embryos and the factors that can assist proper development of embryo.